2017
DOI: 10.1111/1440-1681.12698
|View full text |Cite
|
Sign up to set email alerts
|

β‐eudesmol suppresses allergic reactions via inhibiting mast cell degranulation

Abstract: The regulatory effect of β-eudesmol, which is an active constituent of Pyeongwee-San (KMP6), is evaluated for allergic reactions induced by mast cell degranulation. Phorbol 12-myristate 13-acetate (PMA) plus calcium ionophore A23187-stimulated human mast cell line, HMC-1 cells, and compound 48/80-stimulated rat peritoneal mast cells (RPMCs) are used as the in vitro models; mice models of systemic anaphylaxis, ear swelling, and IgE-dependent passive cutaneous anaphylaxis (PCA) are used as the in vivo allergic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…β-eudesmol was reported to inhibit the production and expression of IL6 through activation if p38 MAPK, NK-κB and caspase-1 in activated human mast cells [36]. Besides, it also reduced serum levels of histamine, IgE, IL1b, IL4, IL5, IL13 and VEGF in the passive anaphylaxis mouse model [37]. Altogether, the results of this study and previous studies suggested that the immunomodulatory effect of AL could be sum of the activity of each component in AL.…”
Section: Discussionmentioning
confidence: 97%
“…β-eudesmol was reported to inhibit the production and expression of IL6 through activation if p38 MAPK, NK-κB and caspase-1 in activated human mast cells [36]. Besides, it also reduced serum levels of histamine, IgE, IL1b, IL4, IL5, IL13 and VEGF in the passive anaphylaxis mouse model [37]. Altogether, the results of this study and previous studies suggested that the immunomodulatory effect of AL could be sum of the activity of each component in AL.…”
Section: Discussionmentioning
confidence: 97%
“…To assess the changes in the level of intracellular calcium with time, HMC-1 cells (1 × 10 5 ) were pretreated with Fura-2/AM in IMDM containing 10% FBS for 30 min, and then harvested as previously described [ 50 , 51 ]. After washing twice with medium containing extracellular calcium chelator EGTA (0.5 mM), the cell suspension (1 × 10 5 cells) was seeded into a 96-well plate and pretreated with LA for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…For fluorescence measurement, fura-2/AM was added in HMC-1 cells (1 × 10 5 /mL) for 30 min. The cells then were harvested to perform the calcium assay as described previously [32].…”
Section: Calcium Assaymentioning
confidence: 99%